Фазовая синхронизация наносекундных генераторов Ганна; Приборы и техника эксперимента; № 6 - Конев В. Ю. Владимир Юрьевич; Губанов В. П. Владимир Павлович; Климов А. И. Алексей Иванович; Ковальчук О. Б. Олег Борисович; Ростов В. В. Владислав Владимирович; Шарыпов К. А. Константин Анатольевич; Яландин М. И. Михаил Иванович (2011, 2011)
Заглавие с экрана